Biodiesel impact on cost, fuel saving and emission reduction for power generation in Malaysia - Tan E.S.; Fauzan N.A.; Yoshikawa K. (Institution of Engineering and Technology, 2023)
Carbon dioxide; Cost reduction; Crude oil; Developing countries; Economic analysis; Electric power system economics; Electric utilities; Emission control; Feedstocks; Fuel economy; Gas turbines; Neutron emission; Biodiesel production; CO2 emission reduction; Crude oil extraction; Economic performance; Feasibility; Fuel savings; Generation; Independent power producers; Biodiesel